Clinical evaluation of a novel transmission detector for 3D quality assurance of IMRT and SBRT. (13th September 2017) - Gueorguiev, Gueorgui; Khan, Fazal; Toomeh, Dolla; Khateri, Deniz; Cotter, Christopher; Young, Michael; Turcotte, Julie Catherine; Crawford, Bruce; Sharp, Gregory; Mahd, Mufeed
Abstract: This work aims at clinically evaluating the performance of a novel transmission detector (TD). The evaluation was done using a comprehensive, structure-specific, patient pre-treatment 3D QA protocol. A total of 19 IMRT and SBRT patient treatment deliveries were measured twice on an Elekta Agility linear accelerator, once with the TD and once with the MatriXX detector for comparison. According to the QA protocol statistical parameters, the results showed good agreement between any pair of the following three doses, treatment planning system computed dose, TD measurement reconstructed dose and MatriXX detector measurement reconstructed dose.